Plasma-catalytic biogas reforming for hydrogen production over K-promoted Ni/Al2O3 catalysts: Effect of K-loading. (October 2022) - Zeng, Yuxuan; Chen, Guoxing; Wang, Jianqiao; Zhou, Rusen; Sun, Yifei; Weidenkaff, Anke; Shen, Boxiong; Tu, Xin
Abstract: Biogas reforming for hydrogen production was achieved in a tabular dielectric barrier discharge (DBD) system using K-promoted Ni/Al2 O3 catalysts with varying potassium loadings. The Ni–K/Al2 O3 catalyst with 2 wt% K loading showed the best reforming performance with a CH4 conversion of 32% and a CO2 conversion of 23%, resulting in the highest energy efficiency of 0.67 mmol kJ −1 among the studied catalysts. In comparison to the unpromoted Ni/Al2 O3 catalyst, the presence of 2 wt% potassium loading enhanced H2 production while suppressing CO formation, increasing the relative amount of H2 in the syngas. Furthermore, the Ni–K/Al2 O3 catalyst (2 wt% K) exhibited the most pronounced plasma-catalytic synergy. The results of thermal gravimetry analysis (TGA) revealed that increasing potassium loading in the catalysts increased carbon production by generating more inactive and less active carbonaceous species ( C γ and C β ) on the catalyst surfaces. This study demonstrates that by tuning the potassium loading of Ni/Al2 O3 based catalysts, the performance of plasma-catalytic biogas reforming at low temperatures can be enhanced. Highlights: Plasma-catalytic biogas reforming over K-promoted Ni catalysts was carried out. Adding 2 wt% K loading to Ni/Al2 O3 showed the best reaction performance. Coupling plasma with Ni–K/Al2 O3 (2 wt% K) exhibited a synergy effect. Increasing K loading enhanced carbon deposition on the catalyst surface. Biogas reforming performance can be tuned by controlling the K loading.